2021
DOI: 10.1038/s43856-021-00033-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic analysis of the causal relationship between aging and COVID-19

Abstract: Background Epidemiological studies revealed that the elderly and those with comorbidities are most affected by COVID-19, but it is important to investigate shared genetic mechanisms between COVID-19 risk and aging. Methods We conducted a multi-instrument Mendelian Randomization analysis of multiple lifespan-related traits and COVID-19. Aging clock models were applied to the subjects with different COVID-19 conditions in the UK-Biobank cohort. We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…82 Another study that was published in a peer-reviewed journal showed accelerated ageing was associated with higher COVID-19 risk, although the publication was not indexed in PubMed. 102 However, there were methodological concerns in some studies, such as interpreting liability as the effect of disease diagnosis, 87 the lack of comprehensive assessment of IV assumptions 96 and insufficient details for replication. 100 …”
Section: Resultsmentioning
confidence: 99%
“…82 Another study that was published in a peer-reviewed journal showed accelerated ageing was associated with higher COVID-19 risk, although the publication was not indexed in PubMed. 102 However, there were methodological concerns in some studies, such as interpreting liability as the effect of disease diagnosis, 87 the lack of comprehensive assessment of IV assumptions 96 and insufficient details for replication. 100 …”
Section: Resultsmentioning
confidence: 99%
“…36 Not only are the elderly up to 90-fold more vulnerable to death from COVID-19, 37 but we and others have previously reported that accelerated biological age is associated with incidence and severity of COVID-19. [38][39][40][41][42] Longitudinal biological age data covering the COVID-19 disease course is also extremely limited.…”
Section: Severe Covid-19 Causes a Reversible Increase In Biological Agementioning
confidence: 99%
“…The likelihood of this happening could be increased in people who already have sub-optimal mitochondrial function associated with a sedentary lifestyle. In this regard, a genetic and phenotypic analysis of the causal relationship between ageing and COVID-19 seems to indicate that accelerated biological ageing is a key factor in susceptibility risk, with both altered Notch signalling and B cell functioning being important [ 19 ].…”
Section: Introductionmentioning
confidence: 99%